DIGENIC TREMATODE INFECTION IN THE EDIBLE OYSTER CRASSOSTREA MADRASENSIS (PRESTON) - Samuel, D (Indian Journal of Fisheries, 2011)
Our knowledge of the trematode parasites on marine animals of Indianwaters is limited. Recently, Silas (1962) reviewed the trematodes parasitic onscomberoid fishes, but, as yet, nothing is known about parasitic larval trematodesin the edible oyster. Mass mortality of oysters due to parasitic cercariais reported from several other places. Howell (1967) observed that the declinein abundanc of oysters in New Zealand beds was largely due to epidemicaloutbreak of Bucephalus longicornutus.